2017
DOI: 10.1097/dbp.0000000000000479
|View full text |Cite
|
Sign up to set email alerts
|

Academic Achievement Deficits and Their Neuropsychological Correlates in Children Born Extremely Preterm

Abstract: Objective The purpose of this study was to examine the risks associated with learning disabilities (LD) in a large sample of children born extremely preterm. We predicted higher than expected rates of LD, particularly in math, and children with LD in math, reading, or both would have lower IQs and specific patterns of neuropsychological deficits. Method We evaluated academic achievement, rates of LD, and their neuropsychological correlates in the Extremely Low Gestational Age Newborn (ELGAN) Study cohort of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
18
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 35 publications
4
18
1
1
Order By: Relevance
“…We predict that this deficit in the preterm group will persist over time, and possibly increase further. In line with this, mathematics deficits have been found in pre-teens (Akshoomoff et al, 2017;Rose et al, 2011), and teenagers (Litt et al, 2012) born preterm. The same applies for other aspects of formal mathematics, such as Set Construction and Number Facts.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…We predict that this deficit in the preterm group will persist over time, and possibly increase further. In line with this, mathematics deficits have been found in pre-teens (Akshoomoff et al, 2017;Rose et al, 2011), and teenagers (Litt et al, 2012) born preterm. The same applies for other aspects of formal mathematics, such as Set Construction and Number Facts.…”
Section: Discussionsupporting
confidence: 62%
“…Very preterm birth (before 33 weeks of gestation) has a negative effect on academic achievement in general (Johnson, Wolke, Hennessy, & Marlow, 2011), and mathematical ability in particular (Akshoomoff et al, 2017;Taylor, Espy, & Anderson, 2009). Every year about 15 million children are born preterm, with preterm birth rates ranging from 5-18% (Liu et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, other potential confounders such as the child's sex were also not associated with systemic inflammation. On the other hand, low birth weight Z‐score, indicative of fetal growth restriction, is associated in this sample with elevated concentrations of some proteins (Landis and Koch, 1977; Leviton et al, 2016) and with low Word Reading scores (Ackshoomoff et al, 2017). Thus, low birth weight Z‐score is a potential confounder.…”
Section: Methodsmentioning
confidence: 87%
“…Children born very preterm (VPT; GA less than 33 weeks) are at increased risk for academic difficulties, and even children without low IQs are more likely than their fullterm (FT)-born peers to have specific learning disabilities or underachievement in reading, spelling, and/or mathematics (Aarnoudse-Moens, Weisglas-Kuperus, van Goudoever, & Oosterlaan, 2009;Litt, Taylor, Klein, & Hack, 2005). Previous studies with independent samples have shown mathematics to be a particular weakness (Akshoomoff et al, 2017;Taylor, Espy, & Anderson, 2009;Taylor, Klein, Drotar, Schluchter, & Hack, 2006). Preschool is an important period in a child's development and early identification of academic weaknesses and targeted intervention are essential to improving outcomes.…”
mentioning
confidence: 99%